2019
DOI: 10.1017/ipm.2019.44
|View full text |Cite
|
Sign up to set email alerts
|

Early intervention services for psychosis in Ireland: are we there yet?

Abstract: Early intervention in psychosis (EIP) services are now a priority for Ireland’s Health Service Executive (HSE). A Model of Care for EIP services has been completed after wide consultation. It has just been launched by the Minister for Mental Health and the aim now is to roll out EIP services throughout the country. The Model of Care outlines the rational, configuration, resources, governance, and quality assurance required to operate EIP services. Two models are recommended. The first is a Hub & Spoke serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…However, an Though the social demography of persons incepted into the three previously reported EIS in Ireland (Lyne et al 2015;Lalevic et al 2019;Murray & O'Connor, 2019) are generally similar to those described here for COPE, it is difficult to make systematic comparisons due to differences in urban versus rural setting, EIS model adopted, structure of the mental health services within which each EIS is embedded, prospective versus retrospective collection of data, presence versus absence of an integrated research component, and scope of reporting operational aspects vis-à-vis clinical evaluations. Though diverse, at this early stage in the journey to EIS in Ireland (Clarke et al 2016;Power, 2019) each has value within its own frame-of-reference and adds to the knowledge base that may assist other mental health services as they move to implement EIS.…”
Section: Operational Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an Though the social demography of persons incepted into the three previously reported EIS in Ireland (Lyne et al 2015;Lalevic et al 2019;Murray & O'Connor, 2019) are generally similar to those described here for COPE, it is difficult to make systematic comparisons due to differences in urban versus rural setting, EIS model adopted, structure of the mental health services within which each EIS is embedded, prospective versus retrospective collection of data, presence versus absence of an integrated research component, and scope of reporting operational aspects vis-à-vis clinical evaluations. Though diverse, at this early stage in the journey to EIS in Ireland (Clarke et al 2016;Power, 2019) each has value within its own frame-of-reference and adds to the knowledge base that may assist other mental health services as they move to implement EIS.…”
Section: Operational Aspectsmentioning
confidence: 99%
“…The journey to EIS in Ireland has been authoritatively reviewed by Power (2019). Establishment of DETECT in 2007 (Omer et al 2010) was a pioneering event that long preceded the Health Service Executive National Clinical Programme for Early Intervention in Psychosis and subsequently facilitated the establishment of a second EIS, the Cavan–Monaghan Mental Health Service (CMMHS) Carepath for Overcoming Psychosis Early (COPE) in 2012 (Nkire et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Health policies in Ireland and internationally have increasingly recognized the necessity for EIS addressing the needs of people experiencing FEP (American Psychiatric Association, 2020; National Institute for Health and Care Excelence (NICE), 2016; Galletly et al, 2016; Power, 2019; Wong, 2012). In Ireland's FEP model of care, keyworkers are valuable members of multidisciplinary teams as they serve as the main point of contact between services and service users, and manage personalized patient care plans (Power, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Health policies in Ireland and internationally have increasingly recognized the necessity for EIS addressing the needs of people experiencing FEP (American Psychiatric Association, 2020; National Institute for Health and Care Excelence (NICE), 2016; Galletly et al, 2016; Power, 2019; Wong, 2012). In Ireland's FEP model of care, keyworkers are valuable members of multidisciplinary teams as they serve as the main point of contact between services and service users, and manage personalized patient care plans (Power, 2019). The value of keyworkers was further highlighted in a recent scoping review (Lim et al, 2020), where they were shown to assume various important responsibilities including coordinating health services, psychoeducation and assisting patients with practical and emotional needs.…”
Section: Introductionmentioning
confidence: 99%
“…The advances made in EI have transformed mental health services and have resulted in improved outcomes for affected individuals and their families. In Ireland, EIP is one of the four National Clinical Programmes (NCP) and was developed in conjunction with the College of Psychiatrists of Ireland Need for early intervention during covid-19 3 (Power, 2019). In 2019, the Health Service Executive funded three EIP demonstration sites in Ireland (Cork, South Lee, Meath & Sligo), bringing the number of EIP services in Ireland up to five (DETECT in Dublin & EIST, Cork North Lee).…”
mentioning
confidence: 99%